Anatomy and Physiology of the Nail Apparatus in the Context of Aesthetic Manicure - Liudmila Yukhymchak (Scientific Trends, 2024)
The nail apparatus is a complex cutaneous appendage comprising the nail plate, nail matrix, nail bed, proximal and lateral folds, cuticle (eponychium), and hyponychium. Its physiological role extends beyond aesthetics: the nail is involved in protecting the fingertip, enabling precise manipulation, and sensory function. Of particular importance for aesthetic manicure are the barrier structures (cuticle/proximal fold and hyponychium), as well as the properties of the nail plate as a " keratin barrier" with a low lipid content and limited permeability. This article systematizes the anatomical and physiological features of the nail apparatus and discusses practical implications for the safe performance of aesthetic manicures.
Keywords: Nail apparatus, matrix, cuticle, hyponychium, nail plate, nail growth, barrier, manicure.